Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic - Grubbs, Scott A.; Dewalt, R. Edward (Zootaxa, 2018)
Perlesta Banks, 1906 (Plecoptera: Perlidae) is a genus of small, summer-emergent stoneflies known primarily from the eastern Nearctic. Thirty-two species are currently recognized, including two from China and nymphs have been reported from Costa Rica. We report here on some cryptic diversity within a small group of Perlesta with dark wings and bodies. Perlesta armitagei sp. nov. is described from the adult male, adult female, and egg. Diagnostic characters are presented with light microscope and scanning electron microscope (SEM) photomicrographs. Perlesta armitagei sp. nov. most closely resembles P. browni Stark, 1989 and P. cinctipes (Banks, 1905), two species distributed mainly within the Interior Highland Region. Perlesta armitagei sp. nov. is known currently within the Ohio River drainage from Indiana eastward to western Pennsylvania and southward into central Kentucky. Comparative light microscope and SEM images are also provided for P. adena Stark, 1989, P. browni, P. cinctipes, and P. xube Stark and Rhodes, 1997 in an effort to better define the morphological concepts of these dark colored species.